Arbejdets æstetik og politik i Stig Sjödins lyrik - Nilsson, Magnus (Passage - Tidsskrift for litteratur og kritik, 2020)
This article analyses one of the most prominent motifs in Swedish working-class writer Stig Sjödin’s (1917-1993) poetry, namely that of work. The main argument is that Sjödin’s attitudes toward work were conditioned both by his Marxist world-view and by the different audiences for which he was writing. The poetry that he published in the labor-movement press aimed at creating class consciousness among workers and presented work both as something marked by oppression and injustice and as a source of pride. In his poetry collections, he presented industrial labor to an audience of non-workers with the aim of making them aware of the plight of the working class. Here, work was presented in a more univocally negative way than in the poetry printed in the labor-movement press.